Homestay online booking system using geofencing technique and geolocation technique / Wan Shafiqah Zaharah Wan Yusof - Wan Yusof, Wan Shafiqah Zaharah (2020)
Malacca i-Homestay, is a mobile application aims to be used as a hub for all the homestays in Malacca, providing the search price feature, making reservation and helping tourist navigate to the homestay. Besides, this application helps users save time and travel cost to get information about the homestay they want to book. This application not only for foreign but also for local tourist who first time come to Malacca. This study provides more valid reasons to build a mobile app using Android with reference to using Waterfall Model as the primary method. This is because of the suitable for long time project. For time to time, the feature will be applied to the system to improve the application's added value. As a platform for this application, the Android operating system has been chosen because Android users are potentially numerous. The result of this project has become an Android mobile application. The application development would be based on the current Homestay application which provides the consumer with a high degree of usability. This way, the user can focus on using the application to directly book a homestay instead of spending time finding a homestay location from the current user location. The system interface will be as simple as possible and user-friendly.